Impact Evaluation of a Special Session Domestic Violence Intervention Program in Connecticut, 2001-2004 - Lyon, Eleanor ([Verlag nicht ermittelbar], 2012)
This study focused on an evaluation of EVOLVE, a newly developed 26-week, 52-session skill building, culturally competent, psycho-educational curriculum-based intervention for male domestic violence offenders with female victims. The curriculum was implemented in three large urban courts that have specialized domestic violence court sessions, judicial monitoring, specialized court staff throughout the judicial process, enhanced advocacy for victims, a collaborative team approach to case processing, and collaboration with networks of involved community service providers. The comparison site (called Explore), also a large urban court, had some specialized court staff and enhanced victim advocacy, as well. It was selected as the comparison because of these court features, the use of a more traditional 26-week intervention (that met just once each week), its high volume, and the high rate of involvement of men of color, which was similar to rates found at the EVOLVE sites at the time the evaluation was proposed. The data file contains 545 cases and 872 variables.